2008
DOI: 10.1007/s11187-008-9163-5
|View full text |Cite
|
Sign up to set email alerts
|

Gibrat’s law and persistence of growth in Greek manufacturing

Abstract: Gibrat’s law, Persistence of growth, Size groups, Age groups, L11, L60, L26,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…In this context, Fotopoulos and Giotopoulos (2010) find that, for Greek manufacturing firms, Gibrat's law is rejected for micro, small, and young firms, while it holds for medium, large, and old firms. Moreover, Daunfeldt and Elert (2013) demonstrated that the more disaggregated the data analysed, the more likely Gibrat's law was to be confirmed.…”
Section: Gibrat's Law: Backgroundmentioning
confidence: 92%
“…In this context, Fotopoulos and Giotopoulos (2010) find that, for Greek manufacturing firms, Gibrat's law is rejected for micro, small, and young firms, while it holds for medium, large, and old firms. Moreover, Daunfeldt and Elert (2013) demonstrated that the more disaggregated the data analysed, the more likely Gibrat's law was to be confirmed.…”
Section: Gibrat's Law: Backgroundmentioning
confidence: 92%
“…Fotopoulos and Giotopoulos (2010) find that, for Greek manufacturing firms, Gibrat's Law is rejected for micro, small, and young firms (with an inverse relation between initial firm size and firm growth), while it is accepted for medium, large, and old firms. Parker et al (2010) find that gazelle growth is significantly affected by a number of strategy variables (see also Mascarenhas et al 2002), such as using customer surveys, selling to other businesses rather than to customers directly, and-more controversially-avoiding issuing shares to workers, directors or other outside investors, and refraining from developing new products.…”
Section: Gibrat's Lawmentioning
confidence: 90%
“…However, what can be done is improving our measures and understanding of the relevant growth processes [see the papers by Parker et al (2010), Leitner and Güldenberg (2010), Bonaccorsi and Giannangeli (2010), and Fotopoulos and Giotopoulos (2010)], and the role of firm strategies in the explanation of firm growth [see the papers by Parker et al (2010), Leitner and Güldenberg (2010), and Park et al (2010)]. In the light of this progress being made, it is remarkable that Gibrat's Law still plays such a prominent role in studies of firm growth.…”
mentioning
confidence: 99%
“…Notwithstanding the abundance of primary research evidence on SME growth and performance (Fotopoulos & Giotopoulos, 2010;Macpherson & Holt, 2007;Payne, Kennedy & Davis, 2009;Stam, 2010), lack of consensus on what constitutes growth and performance as well as their antecedents remains a problem (Audretsch et al, 2014).…”
Section: Studies Two and Three Use Quantitative Analysis Obtained Fromentioning
confidence: 99%
“…Notwithstanding the abundance of primary research evidence on SME growth and performance (Davidsson, Kirchhoff, Hatemi-J & Gustavsson, 2002;Fotopoulos & Giotopoulos, 2010;Gilbert, McDougall & Audretsch, 2006;Macpherson & Holt, 2007;Payne et al, 2009;Stam, 2010), SME owners, managers and policy makers are presented with ambiguous counsel as to the how, when and what to do to ensure on-par or above aspiration level firm performance. To meet this challenge, strategy and entrepreneurship scholars provide highly fragmented and diverse theoretical perspectives with often abstract constructs.…”
Section: Introductionmentioning
confidence: 99%